2022
DOI: 10.1037/xhp0001015
|View full text |Cite
|
Sign up to set email alerts
|

Gaze elicits social and nonsocial attentional orienting: An interplay of shared and unique conflict processing mechanisms.

Abstract: Subtle to no attentional differences have been broadly observed when using gaze and arrows as orienting cues. However, recent studies have found opposite effects when they are used as targets in spatial interference tasks, with arrows eliciting faster responses when their position is congruent with the indicated direction and gaze producing faster responses in incongruent conditions. In two preregistered experiments aimed at exploring the mechanisms supporting these findings, we examined whether the congruency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(64 citation statements)
references
References 54 publications
4
32
4
Order By: Relevance
“…In congruent trials, however, eye-gaze is averted away from the central point of mutual attention, looking at out of the task. Therefore, in congruent trials, it is possible that our attention and eyes are moved outside the task, causing what might be called "joint distraction", i.e., drawing attention outside of the task and therefore increasing RTs (see Hemmerich et al, 2021, for an extended explanation of this hypothesis).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In congruent trials, however, eye-gaze is averted away from the central point of mutual attention, looking at out of the task. Therefore, in congruent trials, it is possible that our attention and eyes are moved outside the task, causing what might be called "joint distraction", i.e., drawing attention outside of the task and therefore increasing RTs (see Hemmerich et al, 2021, for an extended explanation of this hypothesis).…”
Section: Discussionmentioning
confidence: 99%
“…Although Edwards et al (2020) have attributed the RCE to joint attention, i.e., the beneficial effect of both the participant and the gaze to look at the fixation point in incongruent trials, Aranda-Martín et al (2022) have recently shown that the RCE does not appear until late childhood, in spite of joint attention being fully developed much earlier (Mundy et al, 2007). This would leave "joint distraction" (Hemmerich et al, 2021) as the more likely explanation of RCE.…”
Section: Discussionmentioning
confidence: 99%
“…In the gaze spatial Stroop task, a reversed spatial Stroop effect was observed, with shorter reaction times when the gaze direction and its position were incongruent than when they were congruent. The opposite spatial spatial Stroop effects for arrow and gaze targets suggest a unique attentional mechanism for the eye gaze (Cañadas & Lupiáñez, 2012;Edwards et al, 2020;Hemmerich et al, 2022;Ishikawa et al, 2021;Marotta et al, 2018).…”
Section: Introductionmentioning
confidence: 93%
“…Several attempts have been made to explain the reversed spatial Stroop effect (Cañadas & Lupiáñez, 2012;Edwards et al, 2020;Hemmerich et al, 2022;Ishikawa et al, 2021;Marotta et al, 2018), emphasizing the social role of the eye gaze. Cañadas and Lupiáñez (2012) proposed the eye-contact hypothesis (Ishikawa et al, 2021;Marotta et al, 2018).…”
Section: Eye Gaze Is Not Specialmentioning
confidence: 99%
See 1 more Smart Citation